WACANA RANCANGAN MATERI EKONOMI ISLAM DALAM MATA PELAJARAN ILMU PENGETAHUAN SOSIAL DI MADRASAH IBTIDA’IYAH - M. Musyafa M. Musyafa (TARBIYA: Journal of Education in Muslim Society, 2014)
Islamic values should be built in educational institution as early as possible, at least from elementary school. It might be rather difficult to think of Islamic values being taught in the elementary school, especially in social studies subject. One idea was by focusing students learning process on the development of certain values, such as, wealthiness, fairness, honesty, responsibility, and prohibition of practicing usury. Educating the students with those values were believed to contribute to the development of Islamic values in later age. This paper provides some ideas within which the mentioned values were taught in elementary school. DOI: 10.15408/tjems.v1i2.1268